2009
DOI: 10.1161/circep.108.846022
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Endocardial Pacing Improves Resynchronization Therapy in Canine Left Bundle-Branch Hearts

Abstract: Background-We investigated the benefits of the more physiological activation achieved by left ventricular (LV) endocardial pacing (ENDO) as compared with conventional epicardial (EPI) LV pacing in cardiac resynchronization therapy. Methods and Results-In 8 anesthetized dogs with experimental left bundle-branch block, pacing leads were positioned in the right atrium, right ventricle, and at 8 paired (EPI and ENDO) LV sites. Systolic LV pump function was assessed as LVdP/dtmax and stroke work and diastolic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 27 publications
8
75
3
Order By: Relevance
“…Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings emerged from a subanalysis of the REVERSE (Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction) trial 3. These findings are counterintuitive, as previous experimental and clinical evidence shows that an apical LV lead position is more favorable than nonapical positions 4, 5. During normal sinus rhythm in intact myocardium, electrical impulses travel through the rapid conduction system from the His bundle toward the low apex.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Epicardial stimulation from the CS position resulted in an increase in LVdP/ dt of +7.1%±2.5%, whereas from the endocardial counterpart an increase of 6.7%±4.1% was measured, an observation which is in contrast with other studies Van Deursen at al., 2007;Van Deursen et al, 2008). In all nonresponders the increase in LVdP/ dt by CS pacing was below 10%.…”
Section: Hemodynamic Effect Related To Pacing Sitecontrasting
confidence: 95%
“…Van Deursen demonstrated in an acute canine model a superior electrical resynchronization as well as +dP/dT(max) when endocardial biventricular stimulation was used instead of epicardial stimulation. In addition, whereas epicardial stimulation resulted in a transmural dispersion of repolarization, this was not observed in endocardial stimulation (van Deursen et al, 2009). However, Spragg et al compared the hemodynamic effects of endocardial pacing at sites directly transmural to the CS lead tip in a small study of patients and found no difference in hemodynamics (Spragg et al, 2010).…”
Section: Endocardial LV Lead Implantationmentioning
confidence: 99%